Phantom Tales of the Night, Vol 7 (Yen Press, 2022)
I'm tingling all over...to think I'll get to see you writhing in agony again. Murakumo Inn always welcomes the troubled masses, human or otherwise. Only one form of payment is accepted-your most astonishing secrets. The tale this evening is that of a certain youthful writer. Feast upon his suffering as he struggles to "live."...